(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article discusses modern methods of teaching English in secondary schools, their effectiveness, and their importance in the educational process. The study analyzes communicative approaches, interactive teaching methods, innovative pedagogical technologies, and the use of information and communication technologies in English language classes. Special attention is paid to the role of modern teaching strategies in improving students’ speaking, listening, reading, and writing skills.